Dissociation of pulse wave velocity and aortic wall stiffness in diabetic db/db mice: The influence of blood pressure - McCallinhart, Patricia E.; Lee, Yong Ung; Lee, Avione; Anghelescu, Mircea; Tonniges, Jeffrey R.; Calomeni, Ed; Agarwal, Gunjan; Lincoln, Joy; Trask, Aaron J. (Frontiers in Physiology, 2023)
Introduction: Vascular stiffness is a predictor of cardiovascular disease and pulse wave velocity (PWV) is the current standard for measuring in vivo vascular stiffness. Mean arterial pressure is the largest confounding variable to PWV; therefore, in this study we aimed to test the hypothesis that increased aortic PWV in type 2 diabetic mice is driven by increased blood pressure rather than vascular biomechanics. Methods and Results: Using a combination of in vivo PWV and ex vivo pressure myography, our data demonstrate no difference in ex vivo passive mechanics, including outer diameter, inner diameter, compliance (Db/db: 0.0094 ± 0.0018 mm2/mmHg vs. db/db: 0.0080 ± 0.0008 mm2/mmHg, p > 0.05 at 100 mmHg), and incremental modulus (Db/db: 801.52 ± 135.87 kPa vs. db/db: 838.12 ± 44.90 kPa, p > 0.05 at 100 mmHg), in normal versus diabetic 16 week old mice. We further report no difference in basal or active aorta biomechanics in normal versus diabetic 16 week old mice. Finally, we show here that the increase in diabetic in vivo aortic pulse wave velocity at baseline was completely abolished when measured at equivalent pharmacologically-modulated blood pressures, indicating that the elevated PWV was attributed to the concomitant increase in blood pressure at baseline, and therefore “stiffness.” Conclusions: Together, these animal model data suggest an intimate regulation of blood pressure during collection of pulse wave velocity when determining in vivo vascular stiffness. These data further indicate caution should be exerted when interpreting elevated PWV as the pure marker of vascular stiffness.